CHARACTERISTICS OF SOME OBSTETRIC AND GYNECOLOGICAL FEATURES IN PATIENTS WITH POLYCYSTIC OVARY SYNDROME AND CONCOMITANT THYROID GLAND PATHOLOGY - L.A. MEKHDIEVA (Avicenna Tajik State Medical University, 2020)
Objective: To study certain obstetric and gynecological characteristics in patients with polycystic ovary syndrome (PCOS) and hypothyroidism. Methods: Under objections were 100 women of reproductive age with PCOS, which were randomized into two groups depending on the presence or absence of hypothyroidism. The first group included 60 patients with PCOS only, the second group included 40 patients with PCOS and concomitant hypothyroidism, and the control group contained 20 healthy women of reproductive age. The examination included analysis of medical documentation, questionnaires, a physical examination of the pelvic organs with an assessment of the size of the uterus, the thickness of the functional layer of the endometrium, and the volume of the ovaries, echographic examination of the thyroid glands. Results: The analysis of some obstetric and gynecological features in patients with PCOS and hypothyroidism showed a predominance of the number of artificial abortions and spontaneous miscarriages, a high incidence of secondary infertility in anamnesis. When comparing the echographic parameters between the first and second groups, a statistical difference was found in the size of the uterus, which was higher in patients with PCOS and hypothyroidism (p<0.001). Analysis of the results showed that the average volume of the uterus in patients of the first group with PCOS was 29.2±3.11 cm3 , and in patients of the second group with PCOS and hypothyroidism was higher and amounted to 57.3±5.05 cm3 (p<0.001). In comparison between the first and second groups, the values of the ovarian-uterine index were lower in patients with PCOS and hypothyroidism (p<0.05). In all patients, a large number of small (up to 10 mm in diameter) follicles were found in the structure of the ovaries. The ultrasound results in all patients with PCOS showed 3 types of follicle distribution: the peripheral in the form of a «necklace» - in 64 (64%), the diffuse arrangement of follicles - in 28 (28%) and mixed - in 8 (8%). Conclusion: Obtained results characterize some obstetric and gynecological features of patients with PCOS and hypothyroidism.